POTENTIAL APPLICATION OF ROSELLE EXTRACT IN FUNCTIONAL FOOD EMULSIONS [Aplikasi Ekstrak Rosela sebagai Pengemulsi pada Sistem Emulsi Pangan Fungsional] - Nor Hayati Ibrahim; Tan Sook Lee; M. Zul Helmi Rozaini (Jurnal Teknologi dan Industri Pangan, 2013)
ABSTRACT This research was undertaken to investigate the effect of Roselle (Hibiscus sabdariffa. L) extract on the physical properties and stability of extra virgin olive oil emulsions. Four different emulsions were prepared with methanolic Roselle extract (0.01 and 0.02%) and 0.02% BHT (commercial antioxidant) as well as without the extract/ antioxidant (control). The physical properties were studied in terms of pH, droplet size distribution, microstructure, viscosity and stability towards phase separation and lipid oxidation (under accelerated oxidation at 60°C for 10 days). The emulsions with Roselle extract was found to exhibit lower polydispersity and more uniform droplet size as compared to control and BHT emulsions. The highest viscosity was observed for the emulsion with 0.02%. The BHT emulsion was the most unstable towards phase separation after 15 days of storage at 5°C. A protective effect of Roselle extract against lipid oxidation in the emulsions was clearly observed at 0, 2, 8 and 10 days of accelerated storage (at 60°C) with considerably low total oxidation values (5.4 to 13). All emulsions showed insignificant deterioration with peroxide value < 20 meq/kg after oxidation period. This study provided important preliminary data on possibility of applying Roselle extract (which is known to content a significant amount of bioactive compounds) in producing functional food emulsions with acceptable properties and stability. Keywords: antioxidants, emulsion, roselle extract, stability, properties